ANALISIS PENERAPAN PSAK NO. 45 TERHADAP PENYAJIAN LAPORAN KEUANGAN ORGANISASI NIRLABA STUDI KASUS PADA YAYASAN XYZ PONTIANAK TAHUN AJARAN 2010-2011 - B51107036, Raesa Novalita (Jurnal KIAFE, 2012)
In practice, many non-profit organizations who follow the way of financial reporting profit organizations in general, while the defendant was accurate information so that the financial statements easier to understand, has relevance and accountability. The subject matter of this study is to analyze the application of PSAK No. 45 on the financial statements of XYZ Foundation Pontianak and analyze the reasons why the XYZ Foundation has not applied these standards is to find the factors that influence these standards have not been applied The purpose of this study was to determine the application of such standards to the XYZ Foundation and to investigate the factors that menyebabkannnya. The Foundation has not adopted PSAK No. XYZ. 45 in its financial reporting. Form of research is a descriptive case study is to see how the XYZ Foundation presents its financial statements. Data collection techniques are interviews, questionnaires to finance part of the treasurer, as well as documentary study is to learn and record the documents and accounting foundations and other documents relating to the problems studied, techniques of data analysis is the analysis of qualitative analysis techniques form of words, sentences, and pictures describing the scheme of quantitative analisisis. The results of this study extend from the presentation of financial statements that the Foundation has not adopted PSAK No. XYZ. 45, the factors that affect the standard diterapkannnya yet due to various reasons one of them does not understand how compilers of financial statements in accordance with PSAK No.. 45, Foundation XYZ standard financial statements have not been present information elements in complete accordance with PSAK No. 45.